2015
DOI: 10.2967/jnumed.115.165464
|View full text |Cite
|
Sign up to set email alerts
|

Based on the Network Degeneration Hypothesis: Separating Individual Patients with Different Neurodegenerative Syndromes in a Preliminary Hybrid PET/MR Study

Abstract: The network degeneration hypothesis (NDH) of neurodegenerative syndromes suggests that pathologic brain changes distribute primarily along distinct brain networks, which are characteristic for different syndromes. Brain changes of neurodegenerative syndromes can be characterized in vivo by different imaging modalities. Our aim was to test the hypothesis whether multimodal imaging based on the NDH separates individual patients with different neurodegenerative syndromes. Methods: Twenty patients with Alzheimer d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 46 publications
1
44
0
3
Order By: Relevance
“…Hence, it follows that the importance of hypotrophy of such pivotal region such is basolateral nucleus of amygdala in patients with OSA should not be ignored. It is easy to postulate that this deficit must have reverberating impact on the patients’ ability to decipher the very valence of ongoing life experiences and that in others lead to emotional blunting such can be seen in Alzheimer’s disease (AD) or behavioural variant frontotemporal dementia (Rosen et al, 2002, Tahmasian et al, 2015b, Tahmasian et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it follows that the importance of hypotrophy of such pivotal region such is basolateral nucleus of amygdala in patients with OSA should not be ignored. It is easy to postulate that this deficit must have reverberating impact on the patients’ ability to decipher the very valence of ongoing life experiences and that in others lead to emotional blunting such can be seen in Alzheimer’s disease (AD) or behavioural variant frontotemporal dementia (Rosen et al, 2002, Tahmasian et al, 2015b, Tahmasian et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…The function and structure of such networks is of particular interest given that abnormalities in the interactions of network components can play a critical role in neuropsychiatric disorders, with damage to specific functional connectivity nodes and networks giving rise to distinct neurological and psychiatric syndromes (Bassett and Bullmore, 2009, Seeley et al, 2009, Tahmasian et al, 2016, Tahmasian et al, 2015a, Tahmasian et al, 2015b, Tahmasian et al, 2013). The results of our conjunctional meta-analysis point to functionally important co-activation between our seeds (in the right amygdala/hippocampus and right central insula) and the bilateral anterior insula, bilateral thalamus, as well as the posterior-medial frontal cortex (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the Alzheimer Disease Neuroimaging Initiative database, the combination of 18 F-FDG PET and volumetric MR resulted in an accuracy of 91% to classify AD patients from controls (26). In the differential diagnosis of dementing disorders, Tahmasian et al studied the ability of combined 18 F-FDG PET and MR with SVM and found accuracies of 77.5% for AD, 82.5% for frontotemporal dementia, 97.5% for semantic dementia, and 87.5% for progressive nonfluent aphasia (27). The magnitude of accuracies in this setting using either 18 F-FDG or 18 F-FDG plus MR information is in line with our current results for ALS and provide an avenue to optimize the diagnostic performance of 18 F-FDG PET.…”
Section: Discussionmentioning
confidence: 99%
“…The Wellcome Department of Imaging Neuroscience, London, UK) as described previously (Eggers, Schwartz, Pedrosa, Kracht, & Timmermann, 2014;Klupp et al, 2015;Tahmasian, Pasquini, et al, 2015;Tahmasian, Rochhausen, et al, 2015;Tahmasian, Shao, et al, 2015).…”
Section: Preprocessing and Analysis Of Fdg-pet Datamentioning
confidence: 99%